Legal discourse analysis: Foundations of forensic linguistics and its applications in legislation and litigation - Chami, Yassine; Mahdy, Elsoghair; Qutieshat, Enas; Adel, Mohammed A.; Khater, Maya (Research Journal in Advanced Humanities, 2026)
Forensic linguistics has become an exciting area that combines law and linguistics. This study highlights how language, through its precise analysis, can act as valid judicial evidence in resolving legal cases. This paper examines how this field has developed over time, starting with Jan Svartvik’s important contributions in 1968, moving into the professionalisation of the discipline during the 1980s and 1990s, and highlighting its growth in the digital age today. It also examines forensic phonetics, author attribution, discourse analysis, and linguistic profiling, showing how they can be applied in criminal investigations, civil lawsuits, contract interpretation, and safeguarding intellectual property. The authors use a descriptive-analytical approach, supported by comparative case studies, and examine global examples in which linguistic evidence has played an important role. Artificial Intelligence and Large Language Models are able to process a huge amount of data in shorter time compared to humans, yet they still raise important legal and ethical challenges regarding their fairness, transparency, and comprehensibility. This paper had concluded that forensic linguistics has evolved and became a significant component of the legal system. It enhances justice by providing people with the resources to uncover the truth, protect their rights, and comprehend laws more easily.